Caprine herpes virus-1 reduces cell viability and enhances chemosensitivity in breast cancer cells - Iannuzzi, C. A.; Pagano, F.; Tomeo, M.; Sfera, A.; Calabrese, A.; Alfano, L.; Carmerlingo, R.; Cocco, S.; Damiano, S.; Montagnaro, Serena; Ciarcia, R.; Giordano, A.; et al. (Frontiers in Oncology, 2025)
IntroductionOncolytic viruses (OVs) are promising therapeutic agents in oncology that directly lyse tumor cells, modulate the immune response, and alter the tumor microenvironment. Non-human OVs offer advantages over their human counterparts, such as being non-pathogenic in humans and lacking pre-existing immunity. In previous studies, we demonstrated that a non-human caprine herpesvirus 1 (CpHV-1) effectively kills various human cancer cell lines. In this study, we evaluate CpHV-1’s antitumor effects across different breast cancer (BC) cell lines and its potential synergy with FDA-approved BC therapies.MethodsWe assessed the effects of CpHV-1 on BC cell viability and clonogenic potential, cell cycle regulation, and apoptosis in MCF-7, T47D, SKBR3, and MDA-MB-468 cell lines, as well as in non-tumorigenic mammary epithelial cells (MCF-10A). Additionally, CpHV-1 was tested in combination with Abemaciclib, Tucatinib, and Inavolisib, and synergism was evaluated using Chou–Talalay analysis.ResultsOur data show that CpHV-1 induced a dose-dependent cytotoxic effect, with an MOI of 5 reducing viability by ~50% 72 hours post-infection. Clonogenic assays confirmed long-term growth inhibition. We also demonstrated modulation of cell cycle progression and induction of apoptosis in tumor cells mediated by CpHV-1. Finally, combined treatments showed synergy across all BC subtypes, without significant toxicity in normal cells.DiscussionThese findings highlight CpHV-1 as a promising oncolytic agent capable of targeting multiple breast cancer subtypes. Its ability to significantly reduce viability, impair long-term proliferation, and induce apoptosis, together with its synergistic activity when combined with FDA-approved targeted therapies and its limited toxicity in normal cells, supports further investigation of CpHV-1 for breast cancer treatment.